Dynamiques des processus d’enseignement-apprentissage : position du problème et déploiement de contextes - Julie Gobert (Recherches en Éducation)
This research show the importance of the interaction between paradigm register of students and their work of enunciatively position for interpret the elements of a problem-situation. The study presented concerns the construction of natural selection concept in the class of Life and Earth Sciences for students 14-15 years old. The epistemological cognitive and language analyzes give us an understanding of the interpretations students of the problem-situation. The interpretative contexts lead the students to pose some heterogeneous scientific problems, sometimes distant from the problem referred the teacher. Our analyzes provide a better understanding of some of the reasons why sometimes the students’ interpretations of the schoolar situation and its expectations diverge and do not quite match that of the teacher.